Effect of Nanoparticles Seed Treatment on Yield Attributes of Chickpea (Cicer arietinum L) - MK SUSHMA; SHIV K YADAV; S YADAV; R CHOUDHARY; SK LAL; C BHARADWAJ; PK SINGH; Z HUSSAIN; PR KUMAR (Seed Research, 2026)
The studies were carried out on chickpea variety Pusa 547 at ICAR- Indian Agricultural Research Institute, New Delhi during 2020-21 with the objective to the effect of nanoparticles on seed yield attributes. The seeds were dry dressed and infused with each of nano and bulk forms of Zinc oxide, Titanium oxide, Silicon dioxide @ 50, 100, 250, 500 and 750ppm concentrations. Along with the two controls i.e., untreated and treated with recommended PoP (Thiram treated @2g/Kg of seeds), treated seeds were evaluated for seed yield attributes. The result revealed that significantly highest field emergence percentage (90.67%), plant height (53.07cm), number of branches per plant (8.27), number of pods per plant (63.67), seed yield per plant (12.83g), harvest index (39.95) and test weight (24.53g) and lowest days to 50% flowering (125.3 days), were recorded in seed treated with dry nano ZnO @ 250ppm compare to both the controls. The conclusion drawn from the study was that dry nano ZnO @ 250ppm was most effective treatment for enhancement of yield attributes in chickpea.